Feeding Practices among Mothers of Preschoolers in a Selected Community of Pokhara, Nepal - Tamrakar, Rachana; Shakya, Nona (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Feeding practices during the preschool years play a vital role in establishing lifelong dietary habits and health outcomes. Mothers, as primary caregivers, play a central role in determining the quality of children’s diets. The study aimed to assess the feeding practices among mothers of preschoolers in a selected community of Pokhara and examine their association with selected demographic variables. Methods: A descriptive cross-sectional study was conducted among 111 mothers of children aged 3–6 years residing in Ward No. 17 of Pokhara Metropolitan City. Participants were selected using purposive sampling. Data were collected through face-to-face interviews using a structured questionnaire, including socio-demographic details and the Parent Mealtime Action Scale-Revised (PMAS-R). Descriptive statistics, t-tests, and ANOVA were applied using SPSS version 22. Results: Positive persuasion (median=16, IQR=14-17) was the most commonly adopted feeding practice, while coercive methods like insistence on eating were least used (median=7, IQR=5-9). Household income was significantly associated with feeding practice scores (p =0.039), indicating better practices among higher-income groups whereas no significant associations were found with maternal age, education or occupation. Conclusion: Mothers commonly used positive persuasion and provided fruits and vegetables, while reward-based feeding practices remained prevalent. Economic status emerged as an important determinant of feeding behaviors. Community-based nutrition education programs targeting lowincome families are recommended.